2003
DOI: 10.1128/jvi.77.17.9116-9123.2003
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Influenza A Viruses with a Functional Influenza B Virus Neuraminidase or Hemagglutinin

Abstract: Reassortment of influenza

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 30 publications
2
23
1
Order By: Relevance
“…Previously, we successfully generated type A/B chimeric virus, which contained type B HA in a type A virus background, indicating functional compatibility between type A and B HA glycoproteins (Horimoto et al, 2003). In addition, two studies have reported that type B NA can replace the function of type A NA (Ghate and Air, 1999;Flandorfer et al, 2003). Taken together with our current findings, the lack of intertypic reassortants cannot be explained by incompatibilities at the protein level.…”
Section: Discussionsupporting
confidence: 83%
“…Previously, we successfully generated type A/B chimeric virus, which contained type B HA in a type A virus background, indicating functional compatibility between type A and B HA glycoproteins (Horimoto et al, 2003). In addition, two studies have reported that type B NA can replace the function of type A NA (Ghate and Air, 1999;Flandorfer et al, 2003). Taken together with our current findings, the lack of intertypic reassortants cannot be explained by incompatibilities at the protein level.…”
Section: Discussionsupporting
confidence: 83%
“…Parental MDCK and MDCK-HA cells (10 6 cells, 6-well plate format) were trypsinized and stained in suspension as previously described (4). Briefly, cells were washed and incubated with 31C2, PY102, NR-3165, rabbit anti-B/Lee PAb (V-63, 1:1,000) (18), and mouse anti-B/Yam MAb (MAb 15B6, 1:1 of hybridoma TCS) (18) for 30 min at 4°C. After washing 3 times in staining buffer (1ϫ PBS with 5% FBS).…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism governing this segregation is unclear, but intertypic incompatibility at the protein or vRNA level has been hypothesized to be an underlying factor (14)(15)(16). Although recombinant chimeric influenza A/B viruses have been created, suggesting that portions of influenza B virus glycoproteins can replace the function of influenza A virus glycoproteins, substantial genetic modifications of the polypeptides were required for their successful rescue (17)(18)(19). Additionally, the RNA-dependent RNA polymerase (RdRp) of influenza A or B virus has been shown to transcribe genes flanked by the heterotypic promoter sequences (20)(21)(22) found in the terminal noncoding regions (NCRs) of each vRNA (23,24).…”
mentioning
confidence: 99%
“…Chimeric influenza A viruses possessing the HA and NA genes of an influenza B virus have been generated previously by us (12) and others (13). Here, we therefore tested our recently developed influenza A high-yield vaccine candidate (9) with influenza B virus HA and NA genes.…”
Section: Resultsmentioning
confidence: 99%